Analysis of Genetic Variability among thirty accessions of Andean Lupin (Lupinus mutabilis Sweet) using ISSR molecular markers (Scientia Agropecuaria, 2015)
In order to make the genetic variability analysis among thirty accessions of andean lupine (L. mutabilis Sweet) belonging to Agrarian Innovation National Institute (INIA) Seed Bank. DNA was extracted from 300 plants and we made bulks. We standardized amplification protocol of Inter Simple Sequence Repeat (ISSR) primers, we chose the most polymorphic primers to run in acrylamide gel. We found 255 ISSR loci with 8 primers. It was found high genetic variability of the samples under study by ISSR markers. Also observed relatively high polymorphism for autogamous species such as andean lupine. Finally phenograms showed a relationship with the geographical location, possibly due to in situ gene flow due to the exchange or sale of seeds in markets near the collection area.
Keywords: Lupinus mutabilis; bulks; genetic variability; ISSR